3D printed biodegradable polymer reinforced concrete with high structural stability. (May 2023) - Harris, Muhammad; Raza, Ali; Potgieter, Johan; Imdad, Aaqib; Rimašauskienė, Rūta; Mahmood Arif, Khalid
Abstract: The increase in the utilization of non-degradable polymers in the construction industry has raised reservations regarding eco-friendly and energy-efficient building solutions. The contemporary solution is the natural fiber reinforced concrete that registers low structural stability and high water absorption. The low strength is due to the non-homogenous distribution of fibers in composite causing non-uniform load distribution and water absorption is the result of hydrophilicity of natural fibers. This research proposes, for the first time, the manufacturing of biodegradable reinforcements for concrete in specific geometries using 3D printing (fused deposition modeling). The 3D printed reinforcements of polylactic acid concentrate the load in a uniform direction during compressive, flexure, and tensile testing. The reinforcements are tested with respect to different orientations and thicknesses in the concrete composite. The stability to water absorption is investigated using BS 1881 standard followed by post-water absorption compressive testing for concrete composites. The research presents in-situ image analysis for all mechanical characterizations that reveals true fracture behavior along with the validation of mechanical results. The flexure strength shows significant increase to 10.8 MPa as compared to the plain concrete samples. The water absorption test also shows prominent reduction of water absorption to 4.3 % as compared to 7.7 % of plain concrete sample. Overall, the novel reinforced concrete results in superior mechanical properties and moisture stability as compared to the plain (control) concrete and natural sisal fiber reinforced concrete composite.